Tournament structure and nations' success in women's professional tennis - Reid, M.; Crespo, M. N.; Atienza, F.; Dimmock, J. (Journal of Sports Sciences, 2007)
The relationship between domestic professional tournament structure in women's tennis and the subsequent professional ranking success of a nation's female players is examined. The 2003 women's professional tennis tournament calendar provided the distribution of events in 33 countries. Criteria used to classify nations' success in women's professional tennis were as follows: number of players with Women's Tennis Association (WTA) points, number of players with Top 200 rankings, and the combined WTA ranking of a nation's Top 5 female players. Pearson product - moment correlations were performed between the number of tournaments and the three criteria. Considerable variation was observed in the number of events organized between nations (USA, n = 56; Thailand, n = 3). All countries had internationally ranked female players, and 24 nations had players ranked in the Top 200. Results revealed relationships between a nation's number of women's professional events and both that nation's number of professionally ranked players (r = 0.60; P < 0.01) and Top 200 players (r = 0.60; P < 0.01), as well as the combined ranking of their Top 5 players (r = -0.52; P < 0.01). While a similar association was found between the number of professional events and players ranked in the men's game, there was no significant correlation between events held and the combined standing of nations' best five ranked players. Governing bodies and national associations in tennis should consider the provision of professional, domestic competition as key to the development of female tennis players.